2013
DOI: 10.1002/bmc.2956
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a liquid chromatography–tandem mass spectrometry method for topotecan determination in beagle dog plasma and its application in a bioequivalence study

Abstract: Topotecan (TPT) is an important anti-cancer drug that inhibits topoisomerase I. A sensitive and robust liquid chromatography-tandem mass spectrometry (LC-MS/MS) method that potentially determines TPT in beagle dog plasma is needed for a bioequivalence study of TPT formulations. We developed and validated LC-MS/MS to evaluate TPT in beagle dog plasma in terms of specificity, linearity, precision, accuracy, stability, extraction recovery and matrix effect. Plasma samples were treated with an Ostro(TM) sorbent pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…The most abundant (with consistent and stable) fragment ion for multiple reaction monitoring (MRM) was m / z 422.10 → 377.15 for topotecan lactone form and m / z 453.20 → 230.30 for IS. This MRM transition of topotecan lactone form was consistent (as 422.1 → 377 in positive MRM mode) with previous reports [ 22 , 23 ]. Figure S2 shows the relevant mass spectra (including selected precursor and product ions).…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…The most abundant (with consistent and stable) fragment ion for multiple reaction monitoring (MRM) was m / z 422.10 → 377.15 for topotecan lactone form and m / z 453.20 → 230.30 for IS. This MRM transition of topotecan lactone form was consistent (as 422.1 → 377 in positive MRM mode) with previous reports [ 22 , 23 ]. Figure S2 shows the relevant mass spectra (including selected precursor and product ions).…”
Section: Resultssupporting
confidence: 92%
“…The ultraperformance liquid chromatography-electrospray ionization-tandem mass spectrometer (UPLC-ESI-MS/MS) method was preferentially established in this study to quantitatively analyze the lactone or total form of topotecan from biological samples (plasma, urine, feces). The UPLC-ESI-MS/MS assay used in this study was established with reference to previously reported topotecan bioassays [ 22 , 23 ] with some modifications and improvements. In particular, mobile phase composition, gradient elution program, run time, and extraction solvent composition were optimized for our analysis system.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The analytical methods for topotecan quantification in human plasma have involved liquid chromatography almost always with fluorescence detection (Rosing et al, ; Rosing et al, ; Bai et al, ; de Vries et al, ; Vali et al, ) with only two procedures based on mass spectrometry (Baczek et al, ; Li et al, ). However, mass spectrometry was successfully applied also for the determination of TPT in other matrices such as: rat serum (Shin et al, ), rat everted gut sacs (Arellano et al, ), and beagle dog plasma (Ye et al, ). To the best of our knowledge Baczeck et al (2012) was the first to apply mass spectrometry detection for the determination of topotecan in human plasma.…”
Section: Classes Of Anticancer Natural Productsmentioning
confidence: 99%